Порівняльний аналіз впливу розпушувачів на лужність печива - Калина, Вікторія Сергіївна; Троєкурова, Віта Олександрівна; Kalyna, Viktoriia; Troiekurova, Vita (Запоріжжя : Видавничій дім "Гельветика", 2025)
UA: Метою роботи є порівняльний аналіз впливу розпушувачів на лужність печива. Методом сенсорного оцінювання визначено органолептичні показники якості дослідних зразків печива: зовнішній вигляд, колір, запах, смак, консистенція. Стандартним методами проаналізовано зразки за фізико-хімічними показниками якості: лужність. При застосуванні дослідних розпушувачів отримані зразки печива за органолептичними показниками відповідають вимогам ДСТУ3781:2014; найнижчий рівень лужності зафіксовано у зразках, приготованих із використанням розпушувача № 4 (сода харчова та кислота лимонна) = 0,20°; лужність усіх досліджуваних зразків не перевищувала нормативне значення, яке становить 2°. Досліджені розпушувачі є безпечними для використання у технології приготування здобного печива. /// EN: The aim of the work is a comparative analysis of the effect of baking agents on the alkalinity of cookies. In the training laboratory of the Department of Food Technologies of the Dnipro State Agrarian and Economic University, a trial laboratory baking of control samples of shortbread cookies was carried out. The following recipe ingredients were used in baking: wheat flour, butter, sugar, eggs, food additives – baking powder, vanillin, salt. To assess the effectiveness of baking powder and the safety of products, four different types of chemical baking powders were selected and tested: sample 1 – sodium pyrophosphate acid + sodium bicarbonate + corn starch; sample 2 – baking soda E500 + sodium pyrophosphate E450 + wheat flour; sample 3 – baking soda E500; sample 4 – baking soda E500 + citric acid E330. The organoleptic quality indicators of the experimental cookie samples were determined by the sensory evaluation method. All control samples demonstrated the following properties: appearance – regular shape, smooth edges, no bulges on the surface; color – uniform golden; smell – vanilla, characteristic of this type of product; taste – sweet, without foreign flavors; consistency – dry, without compaction, brittle when pressed. The samples were analyzed by standard methods for physicochemical quality indicators: alkalinity. When using the experimental baking powders, the obtained cookie samples by organoleptic indicators meet the requirements of DSTU3781:2014. According to the results of the analysis, the alkalinity level of the experimental cookie samples was established, which characterizes their physicochemical properties and meets the requirements of regulatory documentation: − with baking powder No. 1 − 0.31°; − with baking powder No. 2 − 0.28°; − with baking powder No. 3 − 0.23°; − with baking powder No. 4 − 0.20°. All of the tested baking powders are safe for use in shortbread cookie making.
Comparative analysis of the influence of solvents on the alkalinity of cookies
Keywords: печиво; розпушувачі; харчові добавки; лужність; органолептичні та фізико-хімічні показники якості; cookies; baking powders; food additives; alkalinity; organoleptic and physicochemical quality indicators